Standard versus simplified radiofrequency ablation protocol for Barrett’s esophagus: comparative analysis of the whole treatment pathway - Tan, Wei Keith; Ragunath, Krish; White, Jonathan R.; Santiago, Jose; Fernandez-Sordo, Jacobo Ortiz; Pana, Mirela; Alias, Bincy; Hadjinicolaou, Andreas V.; Sujendran, Vijay; di Pietro, Massimiliano (Endoscopy International Open, 2020)
Background and study aims The standard radiofrequency ablation (RFA) protocol for Barrett’s esophagus (BE) encompasses an intermediary cleaning phase between two ablation sessions. A simplified protocol omitting the cleaning phase is less labor-intensive but equally effective in studies based on single ablation procedures. The aim of this study was to compare efficacy and safety of the standard and simplified RFA protocols for the whole treatment pathway for BE, including both circumferential and focal devices.Patients and methods We performed a retrospective analysis of prospectively collected data on patients receiving RFA between January 2007 and August 2017 at two institutions. Outcomes assessed were: 1) complete remission of dysplasia (CR-D) and intestinal metaplasia (CR-IM) at 18 months; and 2) rate of esophageal strictures.Results One hundred forty-five patients were included of whom 73 patients received the standard and 72 patients received the simplified protocol. CR-D was achieved in 94.5 % and 95.8 % of patients receiving the standard and simplified protocol, respectively (P = 0.71). CR-IM was achieved in 84.9 % and 77.8 % of patients treated with the standard and simplified protocol, respectively (P = 0.27). Strictures were significantly more common among patients who received the simplified protocol (12.5 %) compared to the standard protocol (1.4 %; P = 0.008). The median number of esophageal dilations was one. Conclusion The simplified RFA protocol is as effective as the standard protocol in eradicating BE but carries a higher risk of strictures. This needs to be taken into account, particularly in patients with higher pretreatment risk of strictures, such as those with esophageal narrowing from previous endoscopic mucosal resection (EMR).